Hormonal status and inflammation in menopausal women with bronchial asthma - A. V. Barkova; V. I. Trofimov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2025)
Introduction. At least 348 million patients worldwide suffer from bronchial asthma (BA). It has been established that in women, hormonal status, namely female sex hormones such as estradiol and progesterone, prolactin, luteinizing hormone (LH), follicle-stimulating hormone (FSH), contributes to the course and development of BA.The objective was to evaluate hormonal status and inflammation indices in menopausal women suffering from BA.Methods and materials. Our study involved 71 patients suffering from mild to moderate BA, outside of exacerbation of the disease, in menopause. The control group consisted of 16 healthy menopausal women. All subjects underwent determination of the level of estradiol, progesterone, follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin, cortisol, immunoglobulin E, IL-1α, IL-4 and IL-8, nitric oxide (FENO), cytological examination of spontaneous sputum, as well as spirometry with a bronchodilator.Results. In the group of patients with BA, the level of estradiol was almost 2 times lower compared to the control group (p<0.05), while the level of progesterone was, on the contrary, lower in the control group compared to patients with BA (p<0.05). The level of prolactin was almost 2 times lower in the studied group of patients with BA compared to the control group (p<0.05). A higher level of FSH was found in the group of patients with BA compared to the control group (p<0.05), LH levels were practically the same in the study group and the control group, the LH/FSH level was significantly lower in the study group of patients than in the control group (p<0.05).Conclusion. In all patients, compared to the control group, the estradiol level was significantly lower (p<0.05), although it did not go beyond the established laboratory norms, progesterone, on the contrary, was higher than normal values, and also significantly exceeded the readings of the control group (p<0.05). Probably, such hyperprogesteronemia, not typical for this period of a woman’s life, along with relative hyperprolactinemia, can cause a milder course of BA in our patients and have a favorable effect on the prognosis of the disease.